A New Generation Hybrid Supercapacitor: GO/ZnO - Aydın, Cihat; Yıldız, Oktay Emre (Bitlis Eren Üniversitesi, 2026)
Supercapacitors are energy storage materials used to store higher and larger amounts of charge than known capacitors. Energy density can be increased. Capacity and energy amount can be increased by increasing the amount of surface area used. In this study, graphene oxide (GO) synthesised by Modified Hummers method was reinforced into ZnO synthesised by sol-gel method and hybrid material with supercapacitive properties was produced. XRD, SEM, FTIR, DTA-TGA, UV- Vis-NIR and CV analyses were performed on the produced hybrid nanosupercapacitive composites. It was observed that ZnO particles were located between GO layers and were nano-sized. XRD diffractograms showed hexagonal ZnO crystallographic planes (103), (200), (112), (201), (004) and (202). DTA analyses revealed endothermic peaks due to water loss and organic decomposition. FT-IR analyses confirmed the presence of ZnO and GO in the structure. CV measurements indicate rapid charge transfer at the electrode-electrolyte interface.
Keywords: Composite and Hybrid Materials; Kompozit ve Hibrit Malzemeler